Pharmacotherapy of Behavioral and Psychological Symptoms of Dementia: State of the Art and Future Progress - Magierski, Radoslaw; Sobow, Tomasz; Schwertner, Emilia; Religa, Dorota (Frontiers in Pharmacology, 2020)
The core symptoms of different dementia subtypes are the behavioral and psychological symptoms of dementia (BPSD) and its neuropsychiatric symptoms (NPS). BPSD symptoms may occur at any stage in the case of dementia due to Alzheimer’s disease (AD), whereas they tend to occur early on in the case of its behavioral variant frontotemporal dementia or dementia with Lewy bodies and are essential for diagnosis. BPSD treatment consists of non-pharmacological as well as pharmacological interventions, with non-pharmacological interactions being suggested as first-line treatment. Agitation, psychotic features, apathy, depression, and anxiety may not respond to acetylcholinesterase inhibitors or memantine in AD cases; therefore, antipsychotics, antidepressants, sedative drugs or anxiolytics, and antiepileptic drugs are typically prescribed. However, such management of BPSD can be complicated by hypersensitivity to antipsychotic drugs, as observed in DLB, and a lack of effective pro-cognitive treatment in the case of frontotemporal dementia. The present paper reviews current knowledge of the management of BPSD and its limitations and discusses on-going clinical trials and future therapeutic options.